2022
DOI: 10.5662/wjm.v12.i5.414
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in physicians and final year medical students: A cross-sectional insight into prevalence, self-awareness, and knowledge from Pakistan

Abstract: BACKGROUND Despite its high prevalence, migraine remains underdiagnosed worldwide. A significant reason is the knowledge gap in physicians regarding diagnostic criteria, clinical features, and other clinical aspects of migraine. AIM To measure the knowledge deficit in physicians and medical students and to assess the prevalence of migraine in the same population. METHODS An online questionnaire was developed and distributed among physicians a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…A Pakistani study conducted recently to assess knowledge of migraine in physicians and final-year medical students showed that the knowledge is below the required level. [ 28 ] Less than 50% of the study population agreed that headache is mainly due to neurological manifestation as previously described in the literature. [ 29 ] However, there are not many studies that look at how much primary care doctors know and understand about migraines since it is one of the common types of headaches seen in neurological clinics in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 69%
“…A Pakistani study conducted recently to assess knowledge of migraine in physicians and final-year medical students showed that the knowledge is below the required level. [ 28 ] Less than 50% of the study population agreed that headache is mainly due to neurological manifestation as previously described in the literature. [ 29 ] However, there are not many studies that look at how much primary care doctors know and understand about migraines since it is one of the common types of headaches seen in neurological clinics in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 69%
“…Notably, 89.2% of participants reported experiencing headaches, with a mean severity of 5.1 on a 1-10 scale. A study by Choudry et al (2022) shows that the total prevalence of migraine in physicians and medical students is 24.4% [26]. The variety of reported headache locations and accompanying symptoms such as aura, nausea, and vomiting align with classical migraine features documented in the medical literature.…”
Section: Discussionmentioning
confidence: 75%